2016
DOI: 10.5812/jjm.33235
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in Food Products in Iran: a Review of the Literature

Abstract: ContextMycotoxins are secondary metabolites produced by certain toxigenic fungi and the most of them are aflatoxins, fumonisins, trichothecenes, ochratoxin A, patulin, and zearalenone.Evidence AcquisitionIn consideration of the consumption of certain farm products for animal feed and the prevalence of toxigenic fungi and mycotoxins in food, the present study was performed to evaluate this situation in Iran with a review of the literature using search engines. All published articles were selected using Iran Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The highest concentrations of AFB1 detected during this study in pistachio samples were also comparable to those reported by Hedayati et al . (2016) in their review (53.2 µg kg ‐1 ), while, regarding AFT, the mean levels registered in this survey resulted as comparable to those detected by Al Jabir et al . (2019) in nuts commercialised in Qatar and those described by Macri et al .…”
Section: Resultssupporting
confidence: 87%
“…The highest concentrations of AFB1 detected during this study in pistachio samples were also comparable to those reported by Hedayati et al . (2016) in their review (53.2 µg kg ‐1 ), while, regarding AFT, the mean levels registered in this survey resulted as comparable to those detected by Al Jabir et al . (2019) in nuts commercialised in Qatar and those described by Macri et al .…”
Section: Resultssupporting
confidence: 87%
“…Mycotoxins are secondary metabolites produced by certain toxigenic fungi; the common species are aflatoxins, fumonisins, trichothecenes, ochratoxin A, patulin, and zearalenone [ 32 ]. Among these mycotoxins, the aflatoxins and ochratoxin A were frequently used to induce liver injuries in research.…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%
“…Aspergillus spp. frequently causes human bronchopulmonary infections, mostly in immunocompromised patients ( Hedayati et al, 2016 ; Taghizadeh-Armaki et al, 2017a ; Pinto et al, 2018 ; Omran et al, 2019 ). It causes a broad spectrum of infections including allergic bronchopulmonary aspergillosis, chronic pulmonary aspergillosis, aspergilloma, and invasive aspergillosis, the most serious clinical issue ( Nasri et al, 2015 ; Taghizadeh-Armaki et al, 2017b ).…”
Section: Resultsmentioning
confidence: 99%